Developing and evaluating in vitro effect of pegylated liposomal doxorubicin on human cancer cells - Pham, Thi Minh Hue (2016)
A PEGylated liposomal formulation of doxoburicin has been developed and evaluated with the purpose of reducing toxicity and improving the tumor-targeting efficacy of doxorubicin.PEGylated liposomal doxorubicin was prepared by the lipid film hydration technique using hydrogenated soybean phosphatidylcholine (HSPC) combined with cholesterol and DSPE-PEG . Biological activity and toxicity were tested on A549 and HT 29 cancer cell lines by the MTT method. As the result, the obtained PEGylated liposomal doxorubicin using the lipid film hydration method had an entrapment efficiency of the drug more than 95%. The formulated liposomes were found to be relatively uniform in size (167.8± 3.6 nm) with a negative zeta potential (−27.5 ± 3.5 mV). The stability experiments results indicated that PEGylated liposomal doxorubicinwas stable for at least 3 months at 2-8 2000 o C. The cytotoxic effect of PEGylated liposomal doxorubicin on A549 and HT29 cell lines was effected when the exposure time is over 48h.The A549 cell line was found more sensitive than the HT 29 line to PEGylated liposomal doxorubicin. The lowest IC was observed after 72 hours for both cell lines. These results indicated that PEGylated liposomal doxorubicin was valued to develop as a practical formulation for the tumor-targeting efficacy. Future work will be needed to evaluate the antitumor efficacy of doxoburicin liposome formulation in vivo.